2021
DOI: 10.3390/socsci10050152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trump’s Digital Rhetoric on the US Elections: A View from Worldwide Far-Right Populism

Abstract: A time of turmoil and uncertainty is invading the public sphere. Under the framework of the 2020 US elections, populist leaders around the world supported Trump’s speech on Twitter, sharing a common ideology and language. This study examines which issues (issue frame), and strategies (game frame) framed the messages of populism on Twitter by analyzing the equivalences through Trump’s storytelling and checking the bias of the media in the coverage of the US elections. We selected a sample of tweets (n = 1497) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
0
8
0
6
Order By: Relevance
“…We developed an analysis template (Table 1) with dichotomous and exclusive categories to study the thematic and strategic items used in public communication. The variables derived from previous research about political agenda (Alonso-Muñoz & Casero-Ripollés, 2020;Pérez-Curiel et al, 2021). A content analysis method was used following the adaptation to social networks such as Twitter defined by Crespo (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed an analysis template (Table 1) with dichotomous and exclusive categories to study the thematic and strategic items used in public communication. The variables derived from previous research about political agenda (Alonso-Muñoz & Casero-Ripollés, 2020;Pérez-Curiel et al, 2021). A content analysis method was used following the adaptation to social networks such as Twitter defined by Crespo (2014).…”
Section: Methodsmentioning
confidence: 99%
“…However, the influence of background facts such as Donald Trump's fraud speech in the US elections (Pérez-Curiel et al, 2021) and the conspiracy theories about vaccines, together with the advance of populism (Bennett & Pfetsch, 2018), have led to an increase in citizen disaffection with politics (European Commission, 2018;Tyson et al, 2021). Some governments even contributed to the proliferation of fallacies and hoaxes at the beginning of the pandemic (López-García, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…La televisión como producto de masas en el siglo XX, unido a la proliferación de las tecnologías digitales en el siglo XXI, han generado una mediatización de la política. Por tanto, la comprensión de los asuntos públicos está asociada a la imagen proporcionada por los medios de comunicación (Strömbäck, 2008) y, en la actualidad, por la Red (Pérez-Curiel et al, 2021).…”
Section: Twitter Y La Comunicación Política En Campañaunclassified
“…On Twitter, a large attentive audience can amplify a politician’s message and change or mobilize public opinion ( Zhang et al, 2018 ; Russell, 2021 ). Trump’s rhetoric features many characteristics of populism, including emotional appeals based on opinion rather than fact and allegations of corruption, that attracts followers; indeed, his messages are often picked up by right-wing populist leaders around the world ( Pérez-Curiel, Rivas-de Roca & García-Gordillo, 2021 ). As research on the 2016 presidential campaign illustrates, Trump had an attentive audience, particularly on the far right, that readily amplified his message through retweets ( Zhang et al, 2018 ); a similar phenomenon was found in the 2020 election, for which datasets are gradually assembled and examined ( Abilov et al, 2021 ; Grimminger & Klinger, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such research can reveal abuse of power by dominant groups and resistance by marginalized groups. Given Trump’s populist rhetoric and its potential for spreading disinformation ( Pérez-Curiel, Rivas-de Roca & García-Gordillo, 2021 ), amplification of his messages would have important implications for public discourse. Though critical analysis would require a more detailed and nuanced coding of the tweets than we are able to provide with our methodology, looking at the amplification of political discourse by bots allows us to see the potential manipulation of public discourse, especially if the bots favor one faction, that could affect the power dynamics between parties and have significant negative implications for democracy.…”
Section: Introductionmentioning
confidence: 99%